Pathways to positive scenarios for the Amazon forest in Pará state, Brazil - Siqueira-Gay, Juliana; Yanai, Aurora Miho; Lessmann, Janeth; Pessôa, Ana Carolina M.; Borja, Danilo; Canova, Moara; Borges, Rafael Cabral (Biota Neotropica, 2020)
Abstract: Infrastructure projects and agriculture expansion are increasingly threatening forest conservation in Pará state (Brazil). It becomes necessary to address the implications of these activities on the Amazon complex socio-ecological system, considering both material and non-material aspects of Nature´s Contributions to People (NCP). Multiple studies developed future scenarios for the Amazon, but only a few have focused on discussing positive futures derived from policies and interventions based on conservation and human well-being. Here, we aim at understanding the drivers of forest cover change to produce positive scenarios for the future of the Amazon forest in Pará state. By using the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) conceptual framework, we identified as direct drivers of forest cover change: (i) roads construction; (ii) forest degradation; (iii) hydropower projects; (iv) urban expansion; (v) agriculture and pasture expansion; (vi) rural land occupation; (vii) mining; (viii) climate change. As indirect drivers we identified: (i) energy demand; (ii) population growth; (iii) land prices; (iv) commodity demand; (v) consumption behavior. The development of conservation strategies in the borders of deforested areas is needed given the high demand for Nature´s Contributions to People supply. We also propose policies to address the main drivers of forest cover change, influencing land management and consumption behavior in the state. At last, we envision future positive scenarios that would emerge from policy applications and sustainable actions. Based on our study, we discuss the importance of social learning for developing pathways leading to positive futures that consider the integrity and development of both ecological and social systems.